Safety and tolerability of zonisamide in elderly patients with epilepsy. (15th June 2013) - Trinka, E.; Giorgi, L.; Patten, A.; Segieth, J.
Abstract : Objectives: To assess the safety/tolerability of zonisamide in elderly patients. Materials & methods: A pooled analysis of clinical study data from elderly (≥65 years) patients receiving add‐on/monotherapy zonisamide for partial seizures was compared with pooled adult (18–65 years) study data. Assessments included treatment‐emergent adverse events (TEAEs), clinical laboratory parameters and weight change. Results: Data were analyzed from 95 elderly and 1389 adult patients. Incidence of total TEAEs was similar (elderly, 78/95 [82%] vs adult, 1165/1389 [84%]); but lower in elderly versus adult patients for treatment‐related TEAEs (53/95 [56%] vs 1010/1389 [73%]), severe TEAEs (11/95 [12%] vs 289/1389 [21%]), serious TEAEs (12/95 [13%] vs 230/1389 [17%]) and TEAEs leading to withdrawal (17/95 [18%] vs 312/1389 [23%]). Most TEAEs were of mild‐to‐moderate intensity. TEAEs reported more frequently by elderly versus adult patients included fatigue (11/95 [12%] vs 135/1389 [10%]), nasopharyngitis (8/95 [8%] vs 100/1389 [7%]), constipation (7/95 [7%] vs 67/1389 [5%]) and pruritus (6/95 [6%] vs 29/1389 [2%]). The only serious TEAEs reported by ≥2% of elderly patients were 'convulsions' (4/95 [4%] vs 49/1389 [4%]). Three elderly patients died; one death was considered treatment‐related. TEAEs leading to discontinuation of ≥2% of elderly patients were dizziness (4/95 [4%]), headache (2/95 [2%]), somnolence (2/95 [2%]) and confusional state (2/95 [2%]). For elderly patients, there were minimal changes in clinical laboratory parameters, no reports of respiratory alkalosis or metabolic acidosis and no significant weight changes. Conclusions: Zonisamide demonstrated a favourable safety/tolerability profile in elderly patients. No new or unexpected safety findings were identified.